PENGARUH UPAH MINIMUM KOTA (UMK) TERHADAP INDEKS PEMBANGUNAN MANUSIA KOTA PEKANBARU (2009-2016) - Herman, Herman (Sekolah Tinggi Ilmu Ekonomi Riau, 2018)
The purpose of this research is to see the influence of City Minimum Wage Influence on Human Development Index of Pekanbaru City (2009-2016). The method used in this paper is literature study supported by quantitative descriptive analysis of secondary data. Secondary data used is data development of HDI, district/city minimum wage year 2009-2016 Pekanbaru city. The data are sourced from BPS Pekanbaru, and Bappeda Riau Province. the result of the research shows that the average minimum wage of Pekanbaru city for 8 years (2009-2016) is Rp 1.458.922, while the Human Development Index is only 78.42, in upper-medium category, so that the influence of independent variable to variable tied big enough that is 79.6 percent, so it is clear that the minimum wage of Pekanbaru city needs to be improved